Fabriquer la traite, négocier la protection : échelles, acteurs et enjeux d’un dispositif transnational de contrôle des mobilités (Tunisie, Côte d’Ivoire) - Camille Cassarini (L'Espace Politique)
The fight against human trafficking is one of the key pillars of the Emergency Trust Fund for Africa (ETF) decided following the 2015 Valletta Summit. Tunisia and Ivory Coast have been two recipient states of multiple funds from the ETF. While these two countries have different migration profiles, they are both considered "problematic" from a migration perspective. In addition to the high proportion of Ivorian and Tunisian nationals in the so-called irregular arrivals on European coasts, there has been a continuous increase in the number of Ivorian nationals arriving in Tunisia since 2011. Based on a 16-month ethnographic survey conducted between Tunisia and Ivory Coast, this article aims to analyse the modalities of implementation of the fight against human trafficking in the associative and humanitarian spaces of the two countries by questioning more particularly the forms of mediation and appropriation of these programmes at the local scale. After having restituted the institutional productions of the two countries in the area of human trafficking, it is shown how these programs have been produced and mediated in the two different national contexts. In Tunisia, the fight against trafficking has been translated around the narrative of the democratic transition, while in Ivory Coast, it has been built around child labour. Secondly, we examine the ways in which these programmes are implemented at the local scale, both at the scale of non-governmental organisations and at the scale of community associations. Between diversions for protection purposes and reuses in the fight against immigration, we will examine the diversity of uses of these programmes by associative and humanitarian actors. More generally, this article, while demonstrating the way in which the fight against trafficking has become a new tool of migration control, also contributes to the more general debates surrounding the logics of externalisation and internalisation of the international migration government in Africa.